RESEARCH OF THERMAL STATUS OF THREADING ZONE WITH THE HELP OF FULL FACTOR EXPERIMENT - N. M. Vagabov; A. Z. Kurbanov; M. A. Magomedova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Thermal processing zone status when threading in heatproof, high-strength and titanium alloys is a major problem in the general theory of metal cutting. Under other equal conditions temperature in the processing zone of these materials is higher than in cutting of carbon structural steels, as they have high strength and ductility, low thermal conductivity, that makes difficult the working conditions of the taps, increases the area of the tool contact with the workpiece, deteriorates lubrication and cooling of the cutting area because of the increased tendency of heatresistant materials for the curing. This causes an increase in the work and force of friction and as a consequence the rise of cutting temperature. Research of temperature state of the threaded coils formation zone with combined countersink tool-tap is one of the major challenges facing the authors of this work. When performing the work was used factorial experiment. The temperature in the cutting zone of the thread was determined by a built-in chromel-aluminum thermocouple with thermoelectrode cross-sectional area 0,23mm2 . Experiments were carried out using the apparatus of mathematical statistics. Studies have shown that the greatest impact on the temperature state of the cutting area has a tensile strength of the material. Effect of cutting speed in the studied variation range is relatively less noticeable. The explanation for this is a special scheme of cutting of combined countersink tap which allows significantly improve conditions in the cutting zone. The proposed design of the tap allows to reduce the temperature in the area of tapping for 20%.